Phytotherapeutics oridonin and ponicidin show additive effects combined with irradiation in pancreatic cancer in vitro - Liermann, Jakob; Naumann, Patrick; Fortunato, Franco; Weber, Klaus-Josef; Debus, Jürgen (Radiology and oncology, 2017)
Background: Chemoradiation of locally advanced non-metastatic pancreatic cancer can lead to secondary operability by tumor mass reduction. Here, we analyzed radiomodulating effects of oridonin and ponicidin in pancreatic cancer in vitro. Both agents are ent-kaurane diterpenoids, extracted from Isodon rubescens, a plant that is well known in Traditional Chinese Medicine. Cytotoxic effects have recently been shown in different tumor entities for both agents. Materials and methods: Pancreatic cancer cell lines AsPC-1, BxPC-3, Panc-1 and MIA PaCa-2 were pretreated with oridonin or ponicidin and irradiated with 2 Gy to 6 Gy. Long-term survival was determined by clonogenic assay. Cell cycle effects and intensity of γH2AX as indicator for DNA double-strand breaks were investigated by flow cytometry. Western blotting was used to study the DNA double-strand break repair proteins Ku70, Ku80 and XRCC4. Results: Oridonin and ponicidin lead to a dose-dependent reduction of clonogenic survival and an increase in γH2AX. Combined with irradiation we observed additive effects and a prolonged G2/M-arrest. No relevant changes in the levels of the DNA double-strand break repair proteins were detected. Conclusions: Pretreatment with oridonin or ponicidin followed by irradiation lead to an additional reduction in survival of pancreatic cancer cells in vitro, presumably explained by an induced prolonged G2/M-arrest. Both agents seem to induce DNA double-strand breaks but do not interact with the non-homologous end joining (NHEJ) pathway.